Transformative Pedagogy and Deep Learning Approach in Addressing 21st-Century Educational Challenges - Yuni Misrahayu; Nyoman Dantes; I Made Tegeh (Asian Journal of Applied Education (AJAE), 2026)
This study aims to analyze the implementation of transformative pedagogy and the deep learning approach in addressing the challenges of 21st-century education in higher education institutions in Papua, Indonesia. The study employed a qualitative descriptive approach involving lecturers and students as research informants. Data were collected through semi-structured interviews, classroom observations, and academic documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing systematically. The findings reveal a novel contribution in learning practices, particularly the integration of critical reflection, collaborative discussion, and deep conceptual understanding that enhances student engagement and critical thinking skills. These findings contribute to the development of innovative learning strategies to improve the quality of higher education in Papua.